混合动力电动汽车再生制动能量回收的研究 - 吴普兴; 滕青芳 (Jixie chuandong)
In order to improve the hybrid electric vehicle regenerative braking energy storage efficiency and the efficiency of the system,the characteristics of hybrid electric vehicle regenerative braking and the important factors that affect on energy recovery are analyzed,and the regenerative braking energy recovery strategy is designed based on the fuzzy control,the HEV regenerative braking performance is given full play,the more kinetic energy are translated into electrical energy and stored in the energy storage device.And the simulation is embedded in the ADVISOR software.Simulation experiments with different traffic conditions are carried out,contrasting the battery SOC（state of charge）,it verify the fuzzy logic control strategy is effective and feasible.